The actions of volatile anesthetics: a new perspective. Issue 12 (3rd January 2019) - Weinrich, Michael; Worcester, David L.
Abstract : Recent work applying neutron and X‐ray scattering to elucidate the molecular mechanisms of volatile anesthetics is reviewed. Abstract : This article reviews recent work in applying neutron and X‐ray scattering towards the elucidation of the molecular mechanisms of volatile anesthetics. Experimental results on domain mixing in ternary lipid mixtures, and the influence of volatile anesthetics and hydrostatic pressure are placed in the contexts of ion‐channel function and receptor trafficking at the postsynaptic density.